The effect of family economic education towards lifestyle mediated by financial literacy - Theodora, Berta Dian; Marti’ah, Siti (Dinamika Pendidikan, 2016)
The objectives of the study were to describe the planning, implementation, observation and reflection, to evaluate and identify the constraints and solutions at each cycle and also to find out the learning outcomes achieved with scientific approach through the discovery learning model for 2nd grade students at SMP 2 Kudus. It was a descriptive qualitative study. The research result showed that the studentsâ activity was enough on the first cycle and good on the second cycle. The average mean score of the written test on the first first cycles B- and A- on the second cycle. If it was seen from the minimum completeness criterion (KKM), there were 19 students with the percentage of acquisition was 55% on the 1st cycle and there were 32 students with the percentage of acquisition was 93% on the 2nd cycle. The observation results showed that scientific approach gave improvement of studentsâ activities on the first cycle and the second cycle. The results obtained from the use of scientific approach through the discovery learning model to improve the activity was good, but it needs to be observed continuously on studentsâ attitudes, skills and knowledge in school life.Penelitian ini dilakukan untuk melihat gaya hidup yang dimiliki oleh mahasiswa apakah dipengaruhi oleh pendidikan yang telah diterima dikeluarga dan financial literacy mereka. Serta pengaruh financial literacy sebagai mediasi untuk pendidikan ekonomi dikeluarga terhadap gaya hidup. Sampel dipilih berjumlah 334 dari populasi 2040 mahasiswa Universitas Indraprasta PGRI Jakarta. Teknik analisis data menggunakan path analysis.Deskripsi data diperoleh bahwa 60,78% mahasiswa pada kategori sedangÂ  untuk pendidikan ekonomi dikeluarga, 47%Â  mahasiswa pada kategori tinggi untuk financial literacy dan 58% mahasiswa memiliki gaya hidup tinggi. Penelitian menyimpulkan bahwa (1) pendidikan ekonomi mempengaruhi gaya hidup sebesar 6,4%, (2) financial literacy mempengaruhi sebesar 3,7% terhadap gaya hidup dan (3)Â  pengaruh pendidikan ekonomi dikeluarga melalui financial literacy terhadap gaya hidup sebesar 1,9%. Dapat disimpulkan bahwa financial literacy tidak meningkatkan pengaruh pendidikan ekonomi dikeluarga terhadap gaya hidup. Hasil penelitian akan digunakan sebagai salah satu acuan dalam penerapan perkuliahan kewirausahaan.